Value addition chains central to proposed Livestock Fish Mega Program - Randolph, Thomas F. (International Livestock Research Institute, 2010)
Tom Randolph from ILRI elaborates on the critical notion of value chains in the proposed CGIAR Livestock Fish Mega Program. In the proposal, this results in a focus not just on the farmer, it includes the whole value chain from the farm, the inputs needed by the farmer, to the market, including any additional value adding activities, all the way to the consumer. The new pitch in this proposal is that we are looking at ‘value addition chains’ that produce something for the consumer, something the consumer is willing to pay for. Such value for consumers feeds back through the value chain, creating opportunities, employment, and income that can be captured by the poor. He was speaking in the margins of the CGIAR Livestock Fish Mega Program stakeholder consultation meeting in Addis Ababa, 24 and 25 August 2010